Penguatan Karakter Islam melalui Program Jurnal Membaca di MA NU 06 Cepiring - Masruri; Irawan, Moh Bayu; Hidayatul Auliya, Maulida; Arifa Hafsoh, Zanuba; Satriyani Phalepi, Ayu (Jurnal Pengabdian Kepada Masyarakat, 2025)
Character strengthening is an important agenda in the world of education, especially to produce a generation with good integrity and morality. In the environment of Islamic education, the cultivation of Islamic character is very important. This study aims to analyze the impact of a reading journal on strengthening students' Islamic character at MA NU 06 Cepiring. Using a qualitative approach, research data was collected through observation, in-depth interviews, and document analysis. The findings indicate that the reading journal activity, which is integrated into the curriculum, successfully fosters a sense of discipline and responsibility in students. Moreover, through reflection and summarizing book contents, especially those with Islamic themes, students are able to internalize religious values and apply them in their daily lives. In this context, the reading journal serves as an effective medium for strengthening Islamic character values. This study is expected to be a reference for other educational institutions in developing literacy programs that focus not only on skills but also on character building.